2018
DOI: 10.1002/apj.2186
|View full text |Cite
|
Sign up to set email alerts
|

CO2 desorption tests of blended monoethanolamine–diethanolamine solutions to discover novel energy efficient solvents

Abstract: The CO 2 desorption tests were conducted at 363-378 K for 5.0 mol/L blended monoethanolamine (MEA)-diethanolamine (DEA) solutions to develop the energy efficient solvents with high CO 2 production and low energy consumptions. These desorption tests were performed with a recirculation process for various preloaded, 5 mol/L (4.5 + 0.5 to 0.5 + 4.5) MEA-DEA solutions to find out the optimized solvents with minimum heat duty. Therefore, 1-4 mol/L and 0.5-0.45 mol/L MEA-DEA solvents have larger CO 2 production (nCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(68 citation statements)
references
References 34 publications
6
62
0
Order By: Relevance
“…It is apparent that introducing MEA can enhance CO 2 absorption toward the single amine but deteriorate CO 2 desorption 14 due to its strong carbamate stability and higher energy cost 5 . However, a previous study indicated that blending MEA with DEA (0.5/4.5 or 1 + 4 mol/L) can reach lower heat duty than 5.0 M DEA 18 . The principle of that effect works as follows: Introducing small concentration of MEA will certainly increase heat input Q input to 5–10%, but it will boost CO 2 production to 10%–20% and then reduce heat duty ( H = Q input /nCO 2 ) to 5%–10% 20 .…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…It is apparent that introducing MEA can enhance CO 2 absorption toward the single amine but deteriorate CO 2 desorption 14 due to its strong carbamate stability and higher energy cost 5 . However, a previous study indicated that blending MEA with DEA (0.5/4.5 or 1 + 4 mol/L) can reach lower heat duty than 5.0 M DEA 18 . The principle of that effect works as follows: Introducing small concentration of MEA will certainly increase heat input Q input to 5–10%, but it will boost CO 2 production to 10%–20% and then reduce heat duty ( H = Q input /nCO 2 ) to 5%–10% 20 .…”
Section: Introductionmentioning
confidence: 97%
“…A recent method of solvent improvement was the application of the “coordinative effect” by blending small amount of MEA into secondary amine (DEA) 16–20 or related blended amine solvents (BEA + AMP) since 2019. Liu 17 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An open recirculation-process (Figure S2) vessel equipped with an electrometer [9,26,37] was adopted to conduct the CO 2 desorption tests under atmosphere to extract DEEA and 1DMA-2P solvents at 1.0 mol/L, 1.5 mol/L and 2.0 mol/L, and two types of solid acid catalyst were used as γ-Al 2 O 3 and H-ZSM-5 representing Lewis acids and Brønsted acids [9,26]. The acidic catalytic conditions were 5.0 g, 7.5 g and 10.0 g, This CO 2 desorption process was similar to that of others in the literature [9,26].…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%